PERLINDUNGAN KONSUMEN DALAM PELABELAN PRODUK PANGAN - Sri Agung Arimas, Gusti Ayu; Suharta, I Nengah (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
Article 1 (3) of the Government Regulation 69 of 1999 on Food Labels and Advertising is meant to determine that food labels are : every description of food in the form of drawing, writings, a combination of both or any other form supplied with food, put in, affixed to or a part of food packinging. From the above definition, label can be seen that the information contained on the label. The absence of correct information, clear and honest that should be listed in the labels could mislead consumers and course the legal consequances on actors in the business to be responsible if to harm consumers. It is interesting to examine whether the labeling of food products as stipulated in Government Regulation 69 of 1999 has beed compliance with the principles of consumer protection.
Keywords: Labels, Information, Consumer Rights and Consumer Protection